(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The article describes the construction of model characteristics of morphofunctional indicators and physical fitness of taekwondo players aged 15–17 at the stage of specialized basic training, which are one of the important conditions for controlling and managing the training process of taekwondo players. The purpose of the study is to determine the model characteristics of morphofunctional features and physical fitness of taekwondo players aged 15–17. Model characteristics of taekwondo athletes at the stage of specialized basic training of the 1st and 2nd year of training, according to most indicators, tend to reduce the range of differences between the ideal and minimum values in the training of athletes. A decrease in the ideal indicator of the model characteristics of jumping rope from 138.81 to 36.63 between the first year of study and the second, and a decrease in the range of intervals between the ideal and the minimum by 17.48% was revealed. The research established a decrease in the ideal value of the model characteristics between the first year of study and the second, the indicator of explosive power, the distance test of throwing a tennis ball, from 40.25 to 37.47 m, and the minimum value - from 14.64 to 13.30. Conclusions. The analysis of the model characteristics of the morphofunctional indicators of taekwondo athletes aged 15–17 showed that ideally athletes should have a normosthenic, strong body type and a developed and mobile chest cell, but from the specifics of the sport when dividing athletes by weight categories at competitions, taekwondo athletes have a tall height and a slender physique . Model characteristics of taekwondo athletes at the stage of specialized basic training of the 1st and 2nd year of training, according to most indicators, tend to reduce the range of differences between the ideal and minimum values in the training of athletes. The development of model characteristics of taekwondo players aged 15–17 is one of the important conditions for control and management of the training process of taekwondo players, this will contribute to the rational selection of means and methods of training athletes taking into account their individual characteristics. The conducted studies can be used in the monitoring of preparedness and sports selection of taekwondo players at the stage of specialized basic training.